Education in the Field of Forensic Engineering - Al-Sanjery, Kousay; Fah Tee, Kong; Horng Hean Tee (International Journal of Sustainable Construction Engineering and Technology, 2020)
The profession of forensic engineering has been used in investigations for causes of failure in various engineering cases and used when engineers require to give testimony in judicial proceedings. Forensic engineering has become a field of professional practice of its own; criteria and procedural methods have been proposed in the United States, UK and Europe. Many professionals and engineering institutions have venture in this field and set basic principles to establish a platform for going forward. This paper will cover the topics in design-construction process, design codes and standards, construction safety codes, standards and regulations, the first steps after failure, legal concerns after a failure, standard of care and case studies. It is hoped that the paper will enlighten the scope and details of the forensic engineering discipline which can be used as a tool for a failure knowledge base for engineering education and learning outcomes.